Pengembangan Multimedia Animasi Powtoon Berbasis Konstruktivis Pada Materi Pecahan Sederhana di Kelas IV SD - Azzahra Salma Nabila; Mohammad Faizal Amir (Universitas Pendidikan Ganesha, 2022)
The difficulty of elementary school students in solving simple fractions is because students fail to understand the concept of simple fractions. PowToon's multimedia integration of the constructivist approach is great for facilitating the conception of simple fractions. The purpose of this study was to analyze constructivist-based PowToon animation multimedia (CoPAM) as a valid, practical, and effective learning medium for simple fractions. PowToon was developed using a research and development (R&D) method with a define, design, and development (3-D) model involving 12 fourth grade elementary school students. The data analysis used was descriptive analysis with data collection methods using observation, tests (pre-test and post-test), validation questionnaires (validation of media and material experts, teacher responses, and student responses), and documentation. The results showed that CoPAM had very feasible product criteria in terms of validity, practicality, and effectiveness to facilitate elementary school students in understanding simple fractions. Recommendations for the next study are needed to further develop and test CoPAM products or the like (could go through the dissemination stage) by involving a larger and wider number of participants by testing inferential statistics.